Effect of Virus Infection on Functional Traits of Prunus avium and Prunus cerasus Plants in Nurseries - Pavliuk Liliia; Riaba Iryna; Kryvoshapko Viktoriia; Bublyk Mykola; Bondarenko Pavlo; Udovychenko Kateryna (Journal of Horticultural Research, 2025)
Understanding the effect of viral diseases on plant health is crucial to the successful cultivation of planting material and intensive horticulture of any crop. Our study aimed to investigate the effects of Prunus necrotic ringspot virus (PNRSV) and prune dwarf virus (PDV) on the physiological condition of cherry seedlings. The research subjects were young trees of sweet cherry (Prunus avium L.) ‘Nizhnist’ and sour cherry (Prunus cerasus L.) ‘Bohuslavka’ and ‘Ksenia’. Three types of virus-free rootstocks were budded with virus-free and virus-infected buds of these cultivars and then physiological and biometric parameters were evaluated. Due to virus-induced incompatibility, 100% of virus-infected buds on Krymsk-5 and Krymsk-6 rootstocks were found dead during spring inspection. The survival rate of infected buds on the VC-13 rootstock ranged from 50% to 76.6%, depending on the cultivar. Viral infection negatively affected the physiological parameters of plants, leading to a decrease in chlorophyll a content by 20.9–38.0%, chlorophyll b content by 31.0–43.9%, and a decrease in leaf blade area by 7.6–31.0%, depending on the pathogen and cultivar.